2005
DOI: 10.1097/00008877-200509000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Persistent anxiogenic effects of a single or repeated doses of cocaine and methamphetamine: interactions with endogenous cannabinoid receptor ligands

Abstract: As persistent behavioural changes, such as increased anxiety-related behaviours, can be predicted based on the phenomenon of psychostimulant-induced neuronal plasticity, the time course (3-, 5- and 10-day time points) of the effects of both a single and repeated (daily for 7 days) i.p. administrations of cocaine (COC) and methamphetamine (MA) on anxiety-related behavioural symptoms in the elevated plus-maze test were examined in mice. Furthermore, based on the reported interactions between brain dopamine versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 58 publications
5
40
1
Order By: Relevance
“…Based on animal and human studies, it has been hypothesized that the anxiolytic property of ethanol or, in the case of humans, the belief that alcohol would relieve anxiety, could play a role in the drug-seeking behavior (Thomas et al, 2003) and that anxiety problems precede alcohol abuse (Cox et al, 1990). A recent study has shown that methamphetamine (which also induces long-term damage to dopamine neurons) caused persistent anxiety-related behavioral symptoms lasting for at least 5 days (Hayase et al, 2005). Nevertheless, the current study clearly shows that pretreatment with MDMA does not alter the behavior of the animals in the dark-light box 3 weeks after MDMA, which is the time at which ethanol consumption is greater than that observed in saline-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Based on animal and human studies, it has been hypothesized that the anxiolytic property of ethanol or, in the case of humans, the belief that alcohol would relieve anxiety, could play a role in the drug-seeking behavior (Thomas et al, 2003) and that anxiety problems precede alcohol abuse (Cox et al, 1990). A recent study has shown that methamphetamine (which also induces long-term damage to dopamine neurons) caused persistent anxiety-related behavioral symptoms lasting for at least 5 days (Hayase et al, 2005). Nevertheless, the current study clearly shows that pretreatment with MDMA does not alter the behavior of the animals in the dark-light box 3 weeks after MDMA, which is the time at which ethanol consumption is greater than that observed in saline-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Drug cues also can induce both cocaine craving and anxiety, paired with activation of the hypothalamic-pituitary-adrenal axis (Sinha et al, 2003), suggesting that overlap exists between neural substrates controlling craving evoked by drug cues and stress (Sinha et al, 2000;Weiss, 2005). Finally, the anxiogenic effects of cocaine can be attenuated by CB1 agonists (Hayase et al, 2005). Considering this evidence, one may speculate that the anxiolytic consequences of subchronic treatment with the highest dose of WIN 55,212-2 in the elevated plus maze test may have contributed to the attenuation of anxiogenic effects exerted by environmental cues during the extinction and cue reinstatement tests.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, activation of CB1 receptors seems to attenuate the anxiogenic or stressful aspects of cocaine's actions. For example, anxiogenic effects associated with either single or repeated doses of cocaine in mice were attenuated by the CB1 agonists, CP 55,940, anandamide, 2-arachidonylglycerol, N-arachidonyldopamine, and noladin ether (Hayase et al, 2005). Moreover, recent cannabis use has been found to decrease stress-induced blood oxygen level-dependent (BOLD) signals in the frontal and cingulate cortices of cocaine dependent individuals (Li et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the calming and relaxing properties of cannabis may offset some of the psychological untoward consequences of ATS, such as anxiety and agitation. This possibility is supported by preclinical evidence in rodents subjected to both acute and chronic administration of METH [105]. However, cannabis has been shown to produce variable effects with respect to anxiety [106] and may even exacerbate some of the negative subjective sensations induced by ATSs, such as panic and paranoia.…”
Section: Interactions Of Cannabis and Atssmentioning
confidence: 92%